PENGETAHUAN DAN SIKAP SEBAGAI PREDISPOSISI PERILAKU MEROKOK PADA KOMUNITAS VAPER - I Gede Purnawinadi; Joshua Edward Gerson Kumayas (NUTRIX, 2019)
The Electric cigarette is a device created to convert nicotine into smoke that is different from ordinary cigarettes. World Health Organization (WHO) termed e-cigarettes as Electronic Nicotine Delivery System (ENDS). Smoking behavior can be influenced by various factors including knowledge and attitudes. The purpose of this study was to determine the relationship between knowledge and attitudes with the behavior of electric cigarette users in Airmadidi District. The research design used was an analytic survey with a cross-sectional approach. The sampling technique used was accidental sampling with a sample of 63 respondents who used electric cigarettes. The process of collecting data using a questionnaire, and tested statistically using the Spearman correlation formula with a significant 95% (α <0.05%). The results of the study for the relationship of knowledge and behavior of e-cigarette users showed a value of p = 0.164> 0.05, which means there was no relationship between the knowledge and behavior of e-cigarette users in the District of Airmadidi, while for the relationship of attitudes with the behavior of e-cigarette users showed a value of p = 0, 00 <0.05 with a correlation coefficient (r) of 0.724, which means that there is a significant relationship between the attitudes and behavior of electric cigarette users in Airmadidi District. Recommendations for e-smokers are expected to change attitudes and behavior gradually to avoid the dangers of e-cigarettes. Keywords: Knowledge, Attitude, Behavior, Vaper. Abstrak Rokok elektrik merupakan suatu alat yang diciptakan untuk mengubah nikotin menjadi asap berbeda dari rokok biasa. World Health Organization (WHO) mengistilahkan rokok elektrik sebagai Electronic Nicotine Delivery System (ENDS). Perilaku merokok dapat dipengaruhi oleh berbagai faktor diantaranya adalah pengetahuan dan sikap. Tujuan penelitian ini adalah untuk mengetahui hubungan antara pengetahuan dan sikap dengan perilaku pengguna rokok elektrik di Kecamatan Airmadidi. Desain penelitian yang digunakan adalah survei analitik dengan pendekatan cross-sectional. Teknik sampling yang digunakan adalah Accidental sampling dengan jumlah sampel 63 responden yang menggunakan rokok elektrik. Proses pengumpulan data menggunakan kuesioner, dan diuji statistik menggunakan rumus Spearman correlation dengan signifikan 95% (α <0,05%). Hasil penelitian untuk hubungan pengetahuan dan perilaku pengguna rokok elektrik menunjukkan nilai p=0,164 > 0,05 yang artinya tidak ada hubungan antara pengetahuan dan perilaku pengguna rokok elektrik di Kecamatan Airmadidi, sedangkan untuk hubungan sikap dengan perilaku pengguna rokok elektrik menunjukkan nilai p=0,00 < 0,05 dengan nilai koefisien korelasi (r) 0,724 yang artinya ada hubungan yang signifikan antara sikap dan perilaku pengguna rokok elektrik di Kecamatan Airmadidi. Rekomendasi untuk perokok elektrik diharapkan untuk mengubah sikap dan perilaku secara bertahap agar terhindar dari bahaya rokok elektrik. Kata Kunci: Pengetahuan, Sikap, Perilaku, Vaper.